An analysis of choosing gravity anomalies for solving problems in geodesy, geophysics and environmental engineering - Puškorius, Vytautas; Paršeliūna, Eimuntas; Petroškevičius, Petras; Obuchovski, Romuald (International Conference “Environmental Engineering”, 2020)
Gravity anomalies provide valuable information about the Earth‘s gravity field. They are used for solving various geophysical and geodetic tasks, mineral and oil exploration, geoid and quasi-geoid determination, geodynamic processes of Earth, determination of the orbits of various objects, moving in space around the Earth etc. The increasing accuracy of solving the above mentioned problems poses new requirements for the accuracy of the gravity anomalies. Increasing the accuracy of gravity anomalies can be achieved by gaining the accuracy of the gravimetric and geodetic measurements, and by improving the methodology of the anomalies detection. The modern gravimetric devices allow to measure the gravity with an accuracy of several microgals. Space geodetic systems allow to define the geodetic coordinates and ellipsoidal heights of gravimetric points within a centimeter accuracy. This opens up the new opportunities to calculate in practice both hybrid and pure gravity anomalies and to improve their accuracy. In this context, it is important to analyse the possibilities of detecting various gravity anomalies and to improve the methodology for detecting gravity anomalies. Also it is important the correct selection of the gravity anomalies for different geodetic, geophysical and environmental engineering tasks. The modern gravity field data of the territory of Lithuania are used for the research.
Keywords: gravity anomalies; gravity field; quasigeoid; Free-air gravity anomalies; Faye anomalies; Bouguer anomalies; normal Earth’s gravity field